Apprivoiser l'eau ! Simple ou complexe ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Elle est fugace. Elle est subtile ou violente. Elle est vapeur, liquide ou glace. Elle est indispensable